Vocabulary Learning Through Pictures and Multimedia Technology - Marpaung, Marlin Steffi; Sinaga, Nelly (8ISC Abstract Proceedings, 2022)
Vocabulary is the fundamental aspect of language learning. Students must recall words to learn English well. The aim of this study is to find out that vocabulary learning through pictures and multimedia in group learning is better than individual learning and to find out the students' responses towards the use of multimedia in learning vocabulary. To understand the vocabulary enhancement of the students, this study used a quantitative analysis approach with a comparative design. The instrument used in this study is the vocabulary pre-test and post-test. The sample was VIII grade students from two classes from one of the public schools in Cimahi, Bandung. The result of this study has shown that both groups of students have improved their vocabulary, and students who are taught through multimedia learning in groups are better than students who learn individually, with 59.59 and 59.00 for the pre-test and 83.47 and 73.63 for the post-test. The students' response has shown that most students have responded positively to the use of pictures and multimedia in vocabulary learning. Keywords : group learning, individual learning, vocabulary, technology, CALL